Razvijanje novih meril za ocenjevanje maturitetnih esejev pri splošni maturi iz slovenščine - Čokl, Sonja (Jezik in slovstvo, 2016)
We present a new model for assessing and grading the quality and quantity of knowledge in the essay part of the written exam for one of the most important subjects in the Slovenian general Matura examination: Slovenian as a mother tongue. The model is compared with the current procedure of assessing and grading. The proposed assessment rules are based on key competencies of lifelong learning, while grading is based on a 15-point taxonomically justified grading scale. Using this tool, we assessed the knowledge in an adequate number of selected finished exams in the pre-test examination in the 2014/2015 school year. The grade "good" (3) in the new model is one category higher than it is in the existing grading system. The new model addresses the shortcomings of the present marking system, such as the unsuitable ratio between the "content" and "language" parts of the final grade, the over-extensive 50-point marking scale, the groundless determination of the grading class, the unreliable reassessment of essays, the unfounded dispersion of positive grades, etc. The proposed assessment and the grading model have several advantages: they are simple to use, they operate with taxonomically grounded differences in knowledge, and they use qualitative rules that are absent in the current assessment system, which is noticeably based on the subjective sense and consideration of assessors.
Keywords: Slovene; slovenščina; maturitetni izpiti; splošna matura; vseživljenjsko učenje; Lifelong learning; taksonomija; ocenjevanje; zanesljivost; pravičnost